Number, gender and (genetive) case in English and Spanish - Lorenzana, Amanda Corleto 1939- (s.n.], 1969)
This paper covers the number, gender and case of nouns and of other units in Spanish and English. It attempts to identify the problems that Spanish speakers meet in learning English. The study is conducted in the aim of constructing effective teaching materials for the Spanish learners of English.